Barroom aggression perpetration by Australian women: Associations with heavy episodic drinking, trait aggression, and conformity to gender norms. (2nd November 2017) - Hayley, Alexa; Cox, Elise; Zinkiewicz, Lucy; Graham, Kathryn; Wells, Samantha; Zhou, Jin; Miller, Peter G.
ABSTRACT: Heavy episodic drinking (HED), trait aggression, and conformity to masculine norms increase the risk of barroom aggression (BA) perpetration in men; however, research examining these factors relative to female BA perpetration is lacking. This study assessed the associations of HED, trait aggression, and conformity to masculine and feminine norms with BA perpetration in Australian women. Female university students ( N = 148) aged 18–54 ( Mage = 24.19; SDage = 6.84) completed an online questionnaire including measures of BA perpetration and HED, as well as the Brief Aggression Questionnaire, the Conformity to Feminine Norms Inventory (CFNI), and the Conformity to Masculine Norms Inventory (CMNI). Negative binomial regression analyses found HED, trait aggression, and the Violence and Playboy subscales of the CMNI were positively associated with BA perpetration, while the Domestic and Sexual Fidelity subscales of the CFNI were negatively associated with BA perpetration. Norms supporting the use of violence and having multiple sexual partners are associated with increased likelihood of female BA perpetration, while norms valuing domesticity and monogamy are associated with decreased likelihood of female BA perpetration. These findings suggest BA perpetration by women is related to how much they drink, trait aggression, and socialized gender norms.